1995
DOI: 10.1111/j.1365-2796.1995.tb01181.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of diabetes in family members of probands with non‐insulin‐dependent diabetes mellitus

Abstract: The mother is a more important conduit for inheritance of diabetes than the father in these three ethnic groups. A history of diabetes in pregnancy confers an extra risk to the offspring above this usual maternal excess.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…Remarkably, Simmons et al [19] reported that the maternal predominance was particularly pronounced in the family history of those NIDDM patients who had GD before the onset of NIDDM. Moreover, a maternal excess transmission was also observed on the maternal-grandmaternal side of patients with NIDDM [20].…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, Simmons et al [19] reported that the maternal predominance was particularly pronounced in the family history of those NIDDM patients who had GD before the onset of NIDDM. Moreover, a maternal excess transmission was also observed on the maternal-grandmaternal side of patients with NIDDM [20].…”
Section: Discussionmentioning
confidence: 99%
“…Gestational diabetes mellitus (GDM) and type 2 diabetes have common pathophysiologies, including beta cell dysfunction and insulin resistance. Therefore it is reasonable to assume GDM is also heritable, although direct studies are rare (but see Jaworski et al 1989;Kaprio et al 1992;Simmons et al 1995). Also, genetic variation implicated in liability to Type 2 diabetes has also been implicated in liability to GDM (Shaat et al 2005;Shehadeh et al 2005).…”
Section: Gestational Diabetesmentioning
confidence: 97%
“…www.bjournal.com.br groups (4,(13)(14)(15). Even in the absence of DM during pregnancy, maternal history of DM could be associated with disturbances in carbohydrate metabolism compatible with the presence of insulin resistance in offspring (2,4,6,16).…”
Section: Introductionmentioning
confidence: 99%
“…Even in the absence of DM during pregnancy, maternal history of DM could be associated with disturbances in carbohydrate metabolism compatible with the presence of insulin resistance in offspring (2,4,6,16). Since insulin resistance is also considered to be a risk factor for diabetic micro-and macrovascular complications (17,18), patients with type 2 DM and positive maternal history of DM could be at higher risk of presenting chronic complications of diabetes.…”
Section: Introductionmentioning
confidence: 99%